Design of plastic injection mould of a drainage filter / Aishah Taha and Zulkefli Abu Bakar - Taha, Aishah; Abu Bakar, Zulkefli (1997)
The objective of the project is to design a drainage filter mould for plastic injection. A case study was carried out in relation to all design activities. In the course, material selection, method of design, and time required for the design processes were identified. Cost estimation, method of manufacturing, dimensioning and design concepts were also incorporated. Uni Graphics software was used to design the mould where all concept of the design were translated to the drawing. The complete mould design can be applied in mass production. However, modifications to the original design manufacturing method and process would yield a better result.